Impact of the COVID-19 pandemic on working conditions and mental well-being of mental health professionals in the Netherlands: a cross-sectional study - Stephanie S Leone; Lea J Jabbarian; Tessa J van Doesum; Laura S Shields-Zeeman; Berno van Meijel; Marja van Bon-Martens (BMJ Open, 2023)
Objectives To examine the extent of the impact of the COVID-19 pandemic on the mental health and well-being of mental health professionals (MHPs) in the Netherlands and understand their needs during the COVID-19 pandemic.Design and setting A cross-sectional, mixed-methods study was conducted with MHPs from the Netherlands from June 2020 to October 2020, consisting of an online survey and three online focus group discussions.Participants Participants were MHPs from various occupational groups (psychologists, social workers, mental health nurses, developmental education workers, etc).Primary and secondary outcome measures The online survey included questions about work-related changes due to COVID-19 perceived resilience to stress, changes in lifestyle behaviours and mental health symptoms. The focus group discussions focused mostly on work experiences during the first wave of the COVID-19 pandemic.Results MHP’s reported an increase in experience workload during the pandemic (mean score 8.04 based on a scale of 1-10) compared to before the pandemic (mean score of 7). During the first wave of the pandemic, 50% of respondents reported increased stress, 32% increased sleeping problems and 24% increased mental health problems. Adverse occupational (eg, increased workload OR 1.72, 95% CI 1.28–2.32), psychological (eg, life satisfaction OR 0.63, 95% CI 0.52–0.75), lifestyle (eg, increased sleep problems OR 2.80, 95% CI 2.07–3.80) and physical factors (decline in physical health OR 3.56, 95% CI 2.61–4.85) were associated with a decline in mental health. Participants expressed significant concern in the focus group discussions about the duration of the pandemic, the high workload, less work-life balance and lack of contact with colleagues. Suggestions to improve working conditions included ensuring clear communication about guidelines and facilitating worker contact and support via peer-to-peer coaching where experiences can be shared.Conclusions The current study indicates that MHP experienced a decline in mental health status during the first wave of the COVID-19 pandemic, which should be taken into consideration by employers, policymakers and researchers.